If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -1(3x + -7) = 12 Reorder the terms: 16x + -1(-7 + 3x) = 12 16x + (-7 * -1 + 3x * -1) = 12 16x + (7 + -3x) = 12 Reorder the terms: 7 + 16x + -3x = 12 Combine like terms: 16x + -3x = 13x 7 + 13x = 12 Solving 7 + 13x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 13x = 12 + -7 Combine like terms: 7 + -7 = 0 0 + 13x = 12 + -7 13x = 12 + -7 Combine like terms: 12 + -7 = 5 13x = 5 Divide each side by '13'. x = 0.3846153846 Simplifying x = 0.3846153846
| -5/6x+1=5/18 | | 3y+12=3(4+y) | | -(-5+5p)+6p=-8 | | 8=15-c/3 | | y=7-(1) | | y=7-(0) | | 3p-1=5(9-1) | | 21-7b=-4+5(8b+5) | | y=7-(-1) | | 4(3x-6)=24 | | 6-10x=56-24x | | .5(12x-4)+6=14-10x | | y=-3(3) | | 2(6x-6)=72 | | 14x-(9x-3)=30 | | 1/2*9/2 | | 2ab+4a= | | 7(8+4x)=364 | | 4u=70-3u | | -8(3+r)=-29-7r | | -2(d+5)=-6 | | 82-5x=2x+15 | | 5x+16/9=x/3 | | 15x-(7x-2)=10 | | -23-2x=10x+19 | | 7856x-56=98 | | 5k-6/3=4 | | 7(5x-8)=-231 | | 2-5(2-x)=3(x-4) | | 2x^2+8=20 | | 5k-6/2=5 | | -3x-2=-2x+12 |